2019
DOI: 10.1186/s12887-019-1579-3
|View full text |Cite
|
Sign up to set email alerts
|

A shared protocol for porcine surfactant use in pediatric acute respiratory distress syndrome: a feasibility study

Abstract: Background Pediatric ARDS still represents a difficult challenge in Pediatric Intensive Care Units (PICU). Among different treatments proposed, exogenous surfactant showed conflicting results. Aim of this multicenter retrospective observational study was to evaluate whether poractant alfa use in pediatric ARDS might improve gas exchange in children less than 2 years old, according to a shared protocol. Methods The study was carried out in fourteen Italian PICUs after di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…An Italian multicenter study showed improvements in oxygenation, PaO2/FiO2 ratio, oxygenation index, and pH in a population of children with moderate or severe ARDS caused by multiple diseases [17]. Another multicenter study conducted in Cuba on children with ARDS showed improvements in respiratory parameters and survival [18].…”
Section: Resultsmentioning
confidence: 99%
“…An Italian multicenter study showed improvements in oxygenation, PaO2/FiO2 ratio, oxygenation index, and pH in a population of children with moderate or severe ARDS caused by multiple diseases [17]. Another multicenter study conducted in Cuba on children with ARDS showed improvements in respiratory parameters and survival [18].…”
Section: Resultsmentioning
confidence: 99%
“…Surfactant trials published so far have also quite different key features, and this made data aggregation difficult, especially for pediatric patients. Only recently, a multicenter study led to definition of sharing criteria to administer surfactant in PARDS as compassionate therapy [ 98 ]. Currently ongoing explanatory trials recruit homogeneous populations of infants with bronchiolitis-induced PARDS [ 60 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surfactant is the therapy with the highest level of expectations due to a positive effect in PICU length of stay, but still a few evidence in endpoints such as mortality. A recent study shows that the use of porcine Surfactant improves oxygenation, P/F ratio, and pH in a population of children with moderate or severe pediatric acute respiratory distress syndrome caused by multiple diseases [ 18 ]. In an infant with severe RSV infection, the administration in mechanically ventilated infants with acute respiratory failure due to RSV bronchiolitis improves gas exchange and respiratory and shortens the duration of mechanical ventilation and PICU stay compared with control [ 6 ].…”
Section: Discussionmentioning
confidence: 99%